A flat-joint contact model and meso analysis on mechanical characteristics of brittle rock - Zhou, Yu; Chen, Nengbin; Wang, Li; Wu, Tianhua (Kuwait Journal of Science, 2019)
Abstract: At present, the traditional particle model is difficult to simulate the mechanical characteristics of brittle rock such as particle structure and the ratio of uniaxial tensile to uniaxial compressive strength (σt/σucs). Based upon particle flow theory and particle flow code (PFC), the flat-joint contact model is used to construct the granite meso-analysis model, which can reflect the mineral structure features. The failure modes of rock under uniaxial tension, uniaxial compression and triaxial compression are simulated and compared with the experimental results. The results show that the model has a good performance in the study of brittle rock mechanics and the mechanical mechanism of brittle rock during failure process is deeply revealed from meso mechanical viewpoint. Research also shows that, for hard brittle rock such as granite, the lower ratio of uniaxial tensile to uniaxial compressive strength of the rock can be reproduced by using the flat-joint contact model to construct calculation model, its strength characteristics can be described by using Hoek-Brown strength criterion more reasonably. Key words: granite; brittle; flat-joint contact model; meso; fracture; strength